Product extension services deployment platform - Barata, Diogo Alfaro Cardoso da Gama (2016)
Due to the progresses made in the branch of embedded technologies, manufacturers are becoming able to pack their shop floor level manufacturing resources with even more complex functionalities. This technological progression is radically changing the way production systems are designed and deployed, as well as, monitored and controlled. The dissemination of smart devices inside production processes confers new visibility on the production system while enabling for a more efficient and effective management of the operations. By turning the current manufacturing resources functionalities into services based on a Service Oriented Architecture (SOA), in order to expose them as a service to the user, the binomial manufacturing resource/service will push the entire manufacturing enterprise visibility to another level while enabling the global optimization of the operations and processes of a production system while, at the same time, supporting its accommodation to the operational spike easily and with reduced impact on production. The present work implements a Cloud Manufacturing infrastructure for achieving the resource/service value-added i.e. to facilitate the creation of services that are the composition of currently available atomic services. In this context, manufacturing resource virtualization (i.e. formalization of resources capabilities into services accessible inside and outside the enterprise) and semantic representation/description are the pillars for achieving resource service composition. In conclusion, the present work aims to act on the manufacturing resource layer where physical resources and shop floor capabilities are going to be provided to the user as a SaaS (Software as a Service) and/or IaaS (Infrastructure as a Service).